Rzadki przypadek obumierania podskórnej tkanki tłuszczowej u noworodków - Jadwiga Roszkiewicz; Jolanta Wierzba; Joanna Jagłowska; Aleksandra Wilkowska; Agata Maciejewska-Radomska (Termedia Publishing House, 2011)
Introduction. Subcutaneous fat necrosis of the newborn (SCFN) isa rare disorder of the subcutaneous adipose tissue. Subcutaneous fat necrosis of the newborn usually appears days to weeks after a complicatedperinatal period and the most frequent risk factors are birthasphyxia, birth trauma and meconium aspiration. Clinically, the diseaseis characterized by oedematous lesions evolving into indurated,erythematous plaques and nodules. Skin lesions dissolve spontaneouslyin weeks/months.Objective. To present a rare case of subcutaneous fat necrosis of thenewborn.Case report. Monthly infant, born at time of caesarean due to fluctuationsin heart rate in a state of severe asphyxia. As a cause of respiratorydistress, meconium aspiration syndrome was confirmed. In the firstdays of life transient thrombocytopenia and elevated markers ofinflammation in the laboratory tests were observed. In addition, oedematouslesions evolving into indurated plaques and nodules on theback and upper limbs appeared. Based on a typical clinical picturediagnosis of subcutaneous fat necrosis of newborn was diagnosed.During the 3-month follow-up a spontaneous regression of the skinlesions without scarring was observed.Conclusions. Subcutaneous fat necrosis of the newborn is a rare diseaseusually with mild course. However, in some cases skin may bea visual marker of life-threatening metabolic disturbances such ashypercalcaemia.